2022
DOI: 10.1039/d1ew00320h
|View full text |Cite
|
Sign up to set email alerts
|

Biosolids leachate variability, stabilization surrogates, and optical metric selection

Abstract: Sludge and biosolids organic matter (OM) are increasingly assessed via optical measurements of associated leachates – especially at pilot and bench scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This analysis was computed for actual fluorescence maxima and not pre-set peak regions . Computations on actual fluorescence peak maxima are more accurate in diverse applications because maxima can shift outside classically defined bounds first defined for marine samples. , Based on the slope and response range, Sp A is the best fluorescence peak surrogate for these ash samples and concentrations. However, Sp A typically occurs around ex ≈ 250 nm, which is more susceptible to IFE errors than Sp C at ex ≈ 320–360 nm, an issue further discussed in Section S2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis was computed for actual fluorescence maxima and not pre-set peak regions . Computations on actual fluorescence peak maxima are more accurate in diverse applications because maxima can shift outside classically defined bounds first defined for marine samples. , Based on the slope and response range, Sp A is the best fluorescence peak surrogate for these ash samples and concentrations. However, Sp A typically occurs around ex ≈ 250 nm, which is more susceptible to IFE errors than Sp C at ex ≈ 320–360 nm, an issue further discussed in Section S2 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Korak et al demonstrated that optical metrics do not reflect property balance principles when computed on the slope or shoulders of fluorescence maxima, rather than peak values. Misaligned optical quantification on slopes of wildfire fluorescence signals could reduce detection or differentiation capabilities. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of fluorescence spectroscopy for the study of DOM has gained significant attention over the past 30 years. Three-dimensional fluorescence excitation emission matrices (EEMs) are popularly used to distinguish source origin and inform physicochemical properties of DOM. While fluorescence offers the possibility to collect signals with high sensitivity and relative simplicity, the specific chemical components responsible for DOM fluorescence have yet to be identified . Understanding the chemical characteristics of the main types of fluorophores within DOM would help to address deficiencies in fluorescence analysis, such as spectral overlap between fluorophores and the impacts of local environments on fluorescence signals (see Section S3 in the Supporting Information for an expanded discussion on expected chemical groups responsible for absorbance and fluorescence of DOM).…”
Section: Introductionmentioning
confidence: 99%